Konsep Al-Tazkiyyah dan Konstelasi Pendidikan Karakter untuk Mencegah Kasus LGBT di Indonesia dalam Perspektif Maqasidi Qur’ani: Mafhūm al-Tazkiyyah wa Ĥālatu al-Tarbiyyah al-Sulūkiyyah liman’i “LGBT” bi Indūnīsiyyā ‘alā Nazriyyah Maqāsidi Qur’anī - Mitrajati, Kenyo; Isnaini, Rohmatun Lukluk (Study Program of Arabic Language Teaching, 2023)
This research aims to describe Tazkiyyah as a character education concept for students regarding LGBT cases. This research is qualitative with a library research type and uses a Maqasidi Qur'ani perspective. The research data is the tazkiyyah character education concept with data sources from reference books, e-journals, and lecture materials on language policy and politics. Data collection techniques are carried out using documentation, while data analysis is carried out using content analysis. The research results state: First, there is a debate regarding tazkiyyah in language and the Qur'an. Second, examples of character education educational materials related to LGBT issues are explained systematically. Third, the existence of students' characters related to LGBT is the result of the Tazkiyyah concept.